EV charging/discharging coordination in LV distribution grid - Toh, Wei Le. (2013)
Global warming has always been a problem to the world and it is mainly caused by the emission of the greenhouse gas. Unfortunately, there is quite a significant amount being contributed by human's daily transport, petrol driven vehicles. This is how Electric Vehicles (EVs) came about. There are a few types of electric vehicles namely the Hybrid Electric Vehicle (HEV) and the Plug-in Hybrid Electric Vehicle (PHEV). They have an electrical propulsion system and also an internal combustion engine thus they can rely on both petrol and electricity for power [1]. However, the charging of the EVs will be taxing on the power distribution network due to the huge load imposed by the EVs. This can be improved by using the Optimal Power Flow (OPF) technique to manage power distribution effectively. The objective of this project is to develop an optimal EV charging coordination algorithm and a suitable business model that can be used to enhance the efficiency of the distribution grids. The proposed algorithm should be tested using the Microgrid Energy Management System (MG-EMS) setup in LaCER laboratory. The effectiveness of the proposed algorithm should be assessed in terms of operating cost, cable power losses and voltage deviations of the distribution grid which is a 13-node test feeder. The OPF will be used on several case studies with different loads on the network and also different charging or discharging power of the EV. This is to determine the case with minimum and maximum power loss. Finally, the information collected from the case studies will be used to develop a business strategy for the charging of the EV in the commercial world.